Experimental studies of radar image construction algorithms for propellers and measurement method for repetition frequencies of the blades - S. R. Heister; T. T. Nguyen (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The radar image construction algorithms for propellers of aerial vehicles belonging to the classes «helicopter» and «propeller-driven aircraft» were proposed in [1]. The algorithms are designed to be implemented in a radar sensor with inverse synthesis of antenna aperture. The fundamental condition for the qualitative construction of radar images of the propellers is accurate measurement of their rotation frequency. The measurement method for the repetition frequency of the propeller blades on the base of the convolution of the spectrum of the «secondary» modulation of the signal reflected from propeller was proposed in [2]. This paper discusses the results of experimental studies of the measurement method for repetition frequency of the propeller blades and of the radar images construction algorithms of propellers of typical low-altitude aircraft (helicopters and propeller-driven aircrafts).